Comparative Genetic Mapping Between Octoploid and Diploid Fragaria Species Reveals a High Level of Colinearity Between Their Genomes and the Essentially Disomic Behavior of the Cultivated Octoploid Strawberry - Rousseau-Gueutin, Mathieu (Genetics Society of America, 2008)
Macrosynteny and colinearity between Fragaria (strawberry) species showing extreme levels of ploidy have been studied through comparative genetic mapping between the octoploid cultivated strawberry (F. ×ananassa) and its diploid relatives. A comprehensive map of the octoploid strawberry, in which almost all linkage groups are ranged into the seven expected homoeologous groups was obtained, thus providing the first reference map for the octoploid Fragaria. High levels of conserved macrosynteny and colinearity were observed between homo(eo)logous linkage groups and between the octoploid homoeologous groups and their corresponding diploid linkage groups. These results reveal that the polyploidization events that took place along the evolution of the Fragaria genus and the more recent juxtaposition of two octoploid strawberry genomes in the cultivated strawberry did not trigger any major chromosomal rearrangements in genomes involved in F. ×ananassa. They further suggest the existence of a close relationship between the diploid Fragaria genomes. In addition, despite the possible existence of residual levels of polysomic segregation suggested by the observation of large linkage groups in coupling phase only, the prevalence of linkage groups in coupling/repulsion phase clearly demonstrates that the meiotic behavior is mainly disomic in the cultivated strawberry.